CD20+B LYMPHOCYTES, A HIGHLY INFORMATIVE BIOMARKER FOR EARLY DIAGNOSIS OF CHRONIC ENDOMETRITIS - V. N. Ellinidi (SPb RAACI, 2019)
Plasma cells are often considered to be among important criteria in histological diagnosis of chronic endometritis (CE). Low plasma cell numbers in endometrial stroma, uneven distribution and similarity to the cells of cytogenic endometrial stroma represent difficulties with their identification by routine histological methods of study, and their absence prevents distinct diagnosis of CE. The paper presents data on comparative ROC-analysis of two immunohistochemical parameters of chronic endometritis: CD20+B lymphocytes and CD138+ plasma cells (PC). The study group included 937 women with CE, who were examined for infertility and failed IVF attempts. The control group consisted of 103 women without signs of CE who were studied for male infertility factor.The sensitivity of CD20+B cell assays for the diagnosis of CE was 98% (Se = 0.98), thus being 1.44 times higher compared to the sensitivity of CD138+PC, that was, respectively, 68% (Se = 0.68). The specificity of both indicators for the diagnosis of the absence of CE was high, i.e., 98% (Sp = 0.98), and 99% (Sp = 0.99), respectively. The threshold quantitative values for the two endometrial parameters (cutoff point) for the CE diagnosis were also determined when using CD138+PC-1 cell/5mm2 and CD20+B lymphocytes-5cell/5mm2. Analysis of linear regression showed a highly significant (p = 0.00053) relationship of CD138+ PC from CD20+B lymphocytes: With increased numbers of CD20+B lymphocytes, there is a trend for higher CD138+PC numbers which confirms their direct pathogenetic relationship. The topographic and quantitative features of CD20 B lymphocytes in the endometrium determined during immunohistochemical examination allow us to recommend this approach as a highly sensitive and significant early diagnostic indicator of chronic endometritis.